An Exploratory Discourse on Labour Unrest and Industrial Peace - Nwanne, T. F. I.; Mogboh, V. E. (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
This exploratory discourse is on labour unrest and industrial peace. It was necessitated by the damage done to the nation’s economy by industrial unrest and the urgent need to address the phenomenon. The nation is confronted with a spill-over of bad governance and financial illiteracy in the public sector. The conflict between government and its workers often revolves around inability to pay salaries and fund institutions. A situation where those who teach the future generations are deprived of their living wages; and, political office holders and employers earn in millions officially and unofficially, and teachers earning pittance should be addressed. It is the collective responsibilities of employers and employees to seek to maintain a peaceful and harmonious relationship for improved productivity so as to sustain the nation’s economic growth.